REVITALISASI NILAI-NILAI BUDAYA JAWA PADA SEKOLAH BERBASIS BUDAYA - Sudrajat, Sudrajat (JP (Jurnal Pendidikan) : Teori dan Praktik, 2020)
This research aims to determine the revitalization of values of Javanese culture in schools-based culture in Bantul regency, Yogyakarta. Research used qualitative research method with subject of principal, teacher, officer, and student of SMP Negeri 3 Banguntapan Bantul. Data collection technique was done by interview, observation and documentation. Data analysis using descriptive analysis techniques consist of data collection, data reduction, data display, and verification. The results show that the revitalization of moral values of Javanese culture was done by Petruk strategy (modeling, empowering, teaching, reinforcing, unique, and comprehensive). Schools develop school culture by display of various artifacts and initiating familiar relationships. The culture laboratories built to introduce tools and instruments of Javanese culture. The management of school principal implementing values of leadership satriya (brave), prasaja (simple), setya budya (goodness), and lila (sincerity).